1994
DOI: 10.22358/jafs/69826/1994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzyme supplementation on the digestion of low glucosinolate rapeseed meal in vitro, and its utilization by broiler chicks

Abstract: The effect of 6 commercial enzyme preparations, degrading mainly the non-starch polysac charides, on the nutritional value of low-glucosinolate rapeseed meal (RSM) was evaluated in vitro and in vivo. Solubility of protein, ADF and NDF in RSM incubated with or without the addition of 1% of enzyme was measured in vitro. The protein and amino acid digestibility and metabolizable energy of RSM was determined on 4-weeks old broiler cockerels in a balance experiment, while growth performance was evaluated for 3 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…These NSPs may increase viscosity of digesta and result in decreased nutrient digestibility (Ravindran and Bryden, ; Liang, ). There are no NSP‐degrading enzymes in the digestive tracts of monogastric animals and therefore most nutrients cannot be fully utilized (Alloui et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These NSPs may increase viscosity of digesta and result in decreased nutrient digestibility (Ravindran and Bryden, ; Liang, ). There are no NSP‐degrading enzymes in the digestive tracts of monogastric animals and therefore most nutrients cannot be fully utilized (Alloui et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…While Guenter et al (2001) reported that the use of phytase enzyme in the CMbased diets increased the feed intake. Bedford and Morgan (1995) reported that the addition of enzyme decreased feed intake but, Alloui et al (1994), Kocher et al (20001, Silominski and Campbell (1990) reported that the addition of enzyme did not affect the feed intake.…”
Section: Resultsmentioning
confidence: 99%